Koselleck and the margins of history: anachronism, memory, latency - Rivera García, Antonio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
The concepts anachronism, memory and latency, which in the past were pushed to the margins of historiographical discourse, can be extremely useful in understanding the history that unfolds after the crisis of modernity. Koselleck’s work not only provides the main keys to develop the modern “regime of historicity”, but also helps to understand these three “marginal” concepts. As a historian devoted to the “contemporaneity of the non-contemporary”, he suggests facts and concepts that are both ahead of and behind the time in which they appeared. In his studies about war memorials he has found new historical expressions in which the meaning of the past no longer depends on the future. Furthermore, in disagreement with Gadamer, he has raised the possibility to explain history through categories that are not subject to hermeneutics. The Stimmung of latency Gumbrecht uses to reflect on the end of the modern chronotope belongs to this type of categories.